Depolarization and repolarization parameters on ECG predict recurrence after atrial fibrillation ablation in patients with hypertrophic cardiomyopathy - Wen, Song‐Nan; Zhu, Hao‐Jie; Sun, Peng‐Yu; Wu, Kui; Liu, Nian; Ruan, Yan‐Fei; Bai, Rong; Tang, Ri‐Bo; Yu, Rong‐Hui; Long, De‐Yong; Sang, Cai‐Hua; Jiang, Chen‐Xi; et al. (Journal of cardiovascular electrophysiology, 2019)
Introduction The outcomes of atrial fibrillation (AF) ablation remain suboptimal. It is important to identify which AF patients will most likely benefit from ablation and who are more likely to show treatment failure, especially in those with structural heart disease such as hypertrophic cardiomyopathy (HCM). Methods and Results We enrolled 120 HCM patients who underwent primary AF ablation (48 with persistent AF). Preprocedural QTc was measured and corrected using the Bazett's formula, and the distribution of fragmentation of the QRS complex (fQRS) was recorded. Arrhythmia recurrence was defined as any kind of documented atrial tachyarrhythmia of more than 30 seconds. Overall, arrhythmia recurrence occurred in 69 patients after 13.4 months’ follow‐up. fQRS was present in 71 (59.17%) patients and was most commonly (81.69%) observed in the inferior leads. QTc more than 448 ms could predict arrhythmia recurrence with a sensitivity of 68.1% and specificity of 68.6%. Patients with QTc more than 448 ms (hazard ratio [HR]: 1.982; 95% confidence interval [CI]: 1.155‐3.402; P = .013) or those with fQRS+ (HR: 1.922; 95% CI: 1.151‐3.210; P = .012) were at an increased risk of recurrence. A combination of fQRS+ and QTc more than 448 ms was superior to fQRS or QTc alone in predicting arrhythmia recurrence. Conclusion In patients with HCM undergoing AF ablation, QTc prolongation, specifically >448 ms, and presence of fQRS are independent risk factors for arrhythmia recurrence at follow‐up. The combination of these two parameters has greater predictive value and would help to identify patients who are at the highest risk of procedural failure.